THE INFLUENCE OF VIRAL MARKETING AND ELECTRONIC-WORD OF MOUTH ON THE DECISION TO SUBSCRIBE TO THE NETFLIX APP (Survey on Instagram Followers @netflixid) - Ananto, Yashin Hilmy; Ratnasari, Ina (Jurnal Ecoment Global, 2025)
Objectives: This research aims to test and analyze the effect of viral marketing and electronic word of mouth on the Netflix application purchasing decision. This study uses primary data obtained from the results of distributing questionnaires to Netflix Indonesia Instagram followers (@netflixid) Design/Methods/Approach: The method used is descriptive and verification with a quantitative approach. The sample in this study were 384 samples from 1,400,000 population taken using nonprobability sampling method with purposive sampling technique. The analysis technique used in this research is scale range analysis and multiple linear regression analysis and SPSS 26 Software. Findings: The results showed that viral marketing, electronic word of mouth, and subscription decisions in the Netflix application are in the excellent category, meaning that the viral marketing run by Netflix is considered capable of satisfying its users so that these users share their experiences online and influence other users to decide to subscribe. Partially, viral marketing has a positive and significant effect on subscription decisions, electronic word of mouth has a positive and significant effect on subscription decisions. Originality/Value: No previous studies on viral marketing and electronic word of mouth have been conducted on Netflix application subscribe decision. Practical/Policy Implication: Improving the quality of the reviews displayed and their relation to user preferences, Netflix can generate more positive responses and increase the overall positive perception of the app and content. Netflix can improve the quality and variety of its content by ensuring that the content presented has consistency in terms of story, cinematography, and genre diversity. Strategies such as providing original content relevant to local preferences can be implemented to attract subscribers so that users will feel more confident and satisfied with their decision to subscribe. In addition, free trials or subscription discounts can be offered to encourage hesitant subscribers.   Keywords: Viral Marketing, Electronic Word of Mouth, Decision